Building Democracy… Which Democracy? Ideology and Models of Democracy in Post-Transition Latin America - Munck, Gerardo L. (2017)
Politics in Latin America continued to be about democracy after the democratic transitions in Latin America in the 1980s and 1990s. An old concern –securing the minimal standard of democracy that had served as the goal of democratic transitions –remained relevant. But a new concern –the attainment of more than a minimal democracy– transformed politics about democracy. Actors who supported and opposed neoliberalism –the key axis of ideological conflict– advocated and resisted political changes in the name of different models of democracy. And the conflict over which model of democracy would prevail shaped Latin America’s post-transition trajectories, determining how democracy developed and, in turn, whether democracy endured.